2019
DOI: 10.1080/14786419.2019.1577833
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxing effect and possible chemical markers of the flowers of the Mexican Crataegus gracilior

Abstract: The vasorelaxing effect of the methanol extract of the flowers of Crataegus gracilior, a Mexican medicinal plant used to treat some cardiovascular diseases, was assessed, and its possible chemical markers identified. The extract produced a potent vasodilator effect on isolated rat aortic rings (EC 50 = 1.83 ± 1.39 µg/mL; E max = 100 ± 3.4%). Vitexin, the most commonly identified flavonoid in the flowers and used to standardise some Crataegus species, was not found at all in this plant sample. Instead, daucoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…PCTs can be found in the aerial parts, stems, and resin of the identified plants, which must be dried and milled prior to the extraction procedures. Usually, for extraction, organic solvents are used for the extract preparation as binary mixtures, dichloromethane (CH 2 Cl 2 ), hexane (C 6 H 14 ), chloroform (CHCl 3 ), and methyl alcohol (CH 3 OH) are the most adopted solvents [31,[35][36][37][38]41,50]. The main extraction techniques used for PCTs from Mexican plants are maceration and Soxhlet extraction [30,37,39,47].…”
Section: Extraction and Purification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCTs can be found in the aerial parts, stems, and resin of the identified plants, which must be dried and milled prior to the extraction procedures. Usually, for extraction, organic solvents are used for the extract preparation as binary mixtures, dichloromethane (CH 2 Cl 2 ), hexane (C 6 H 14 ), chloroform (CHCl 3 ), and methyl alcohol (CH 3 OH) are the most adopted solvents [31,[35][36][37][38]41,50]. The main extraction techniques used for PCTs from Mexican plants are maceration and Soxhlet extraction [30,37,39,47].…”
Section: Extraction and Purification Methodsmentioning
confidence: 99%
“…Additionally, methanolic extract of flowers from Crataegeus gracilior presented vasorelaxant effects on rat aortic rings [50]. The extract had an EC 50 of 1.83 ± 1.39 µg/mL and an E max of 100 ± 3.4%, being 5-fold more potent than the positive control acetylcholine (ACh) (EC 50 of 9.77 ± 0.81 µg/mL and an E max of 66.72 ± 1.07%).…”
Section: Biological Activity Survey Of Pcts Found In Mexican Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the extract possessed a concentration-dependent vasodilator property, and the authors suggested that the main agent responsible for that activity was CO. However, contributions of other flavonoids and triterpenes could not be excluded [88].…”
Section: Corosolic Acidmentioning
confidence: 99%
“…Regarding the chemical composition of Mexican Crataegus species, chlorogenic acid, (+)-catechin, (-)-catechin, quercetin, kaempferol and apigenin glycosides have been identified in the ethanolic extracts obtained from the fruits of C. stipulosa , C. mexicana , C. nelsoni ( García-Mateos et al, 2013 ) and C. pubescens ( González-Jiménez et al, 2018 ) . Additionally, ursolic, corosolic and euscapic acids have been identified in the methanolic extracts obtained from the leaves and flowers of C. gracilior ( Hernández-Pérez et al, 2014 , Torres-Ortiz et al, 2019 ). Both extracts showed antioxidant effect and elicited a significant vasodilator activity.…”
Section: Introductionmentioning
confidence: 99%